(untitled) (Indian Journal of Animal Production and Management, 2025)
This experiment was conducted at the Department of Animal Production, Faculty of Agriculture, University of Karbala, between November 10, 2023, and December 22, 2023, to study the effect of adding marjoram water extract to drinking water on the production performance of broiler chickens. The study aimed to determine the effect of adding different levels of Origanum majorana powder extract to feed on the productive performance of broiler chickens and some blood components. One hundred and fifty 7-day-old Ros 308 chicks were used, and the experiment lasted 35 days. The birds were randomly distributed into four treatments, with 60 chicks per treatment. The chicks were fed starter and finisher feeds with crude protein levels of 23% and 21.5% and energy levels of 3027 and 3195.3 kcal/kg of feed, respectively. An aqueous extract of marjoram was added at the following rates (20 ml/l rinking water) for the second group. 30 ml/l drinking water) for the third group. (40 ml/l drinking water) for the fourth group. The first group (control) was given normal drinking water without any additives The results of the experiment indicated significant increase (p<0.05) in live body weight (2562.2693 g/bird) for the two levels (40 ml extract/l drinking water) and (30 ml extract/l drinking water) compared to the control group. The addition of the extract improved feed conversion efficiency. The addition led to a significant increase (p<0.05) in cumulative (total) feed consumption for the third and fourth treatments. The addition did not significantly affect the amount of feed consumed by the second group (20 ml extract/l drinking water). Based on the results obtained from the study, it is possible to use marjoram extract in drinking water